(untitled) (Boletin Médico de Postgrado, 2020)
Cancer is the second cause of death around the world, representing melanoma 1% of all cancer. It has been suggested that cancer is a systemic inflammatory disease that generates free radicals causing mutations and releasing trophic factors that favors tumor initiation and cell proliferation. In order to study the effect of formalin-induced inflammation on the development of B16 melanoma, 22 Balb/C mice were divided into three groups: Control Melanoma (CM), Melanoma-Formalin (MF) and Control Formalin (CF). CF and MF groups were injected with 20 μl of 2% formalin on the back of the right paw at the subcutaneous level; CM and MF groups were transplanted with 100,000 melanocytic cells subcutaneously in the plantar surface of the right paw, 24 hours after formalin. CF group mice developed an inflammation that was maximal between the first and second week, then progressively diminished until disappearance by the sixth week. CM group mice developed tumoral macules up to 30 mm², which involute spontaneously. MF group mice developed tumor masses that reached up to 300 mm³ between 3-4 weeks post-transplant and then progressively decreased in volume. CF and MF mice significantly decreased in weight with respect to CM group. In conclusion, inflammation induced by formalin favors tumor development in an allogenic model of malignant melanoma, indicating that anti-inflammatory treatments may be useful in the management of melanoma.